Analysis of the Waste Bank Management Model in Manado City to Support the Concept of Sustainable Development - Lumeno, Shirly Susanne; Warouw, Felly Ferol; Kembuan, Djubir R.E. (JR Education, 2025)
The waste problem is very worrying because it has a direct impact on humans, especially the entry of plastic elements into the human body through fish and food exposed to microplastics. One way to solve the waste problem is to reduce waste from the source by sorting it from the source and further managing it through recycling or upcycling into new products. Reducing waste from the source by sorting it and then saving it in the Waste Bank is one of the promising breakthroughs and can encourage people to actively participate in environmental management. The purpose of this study was to obtain a model for mapping the waste management service area in Manado City as needed. The research data was obtained through research on smash applications for waste banks and field research through observation and interviews. The data were analyzed by mapping the position of the waste bank in the city of Manado. Next, compare the three waste banks in the city of Manado to find the pattern of waste bank management with various indicators. The results showed that the current position mapping of the waste bank in Manado City consists of the center, the outskirts, and the outskirts of the city. Furthermore, the results of the comparison of the three waste banks resulted in a conclusion about the most effective waste bank, namely the waste bank in the residential area. An effective waste bank is one of the strategies for implementing 3R (Reuse, Reduce, Recycle) in waste management at the source at the community level. The implementation of the waste bank, in principle, is a social engineering to invite the public to sort waste for environmental sustainability and community welfare.